2019
DOI: 10.5530/pc.2019.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Brachychiton rupestris (T.Mitch. ex Lindl.) K. Schum. Extracts Inhibit the Growth of Streptococcus pyogenes

Abstract: Introduction: Streptococcus pyogenes is a gram positive pathogenic bacterium which causes a variety of diseases including streptococcal pharyngitis, impetigo and rheumatic heart disease. Many Brachychiton spp. have reported uses to treat pathogenic illness and are rich in flavonoids with reported antibacterial activity. Despite this, B. rupestris leaf extracts have not previously been examined for bacterial growth inhibitory properties. Methods: The ability of B. rupestris leaf extracts to inhibit the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Non-targeted GC-MS headspace analysis. As previously described [17][18][19][20][21] , separation and quantification of phytochemical components were performed using a Shimadzu GC-2010 plus (USA) linked to a Shimadzu MSTQ8040 (USA) mass selective detector system as previously described 22 . Briefly, the system was equipped with a Shimadzu auto-sampler AOC-5000 plus (USA) fitted with a solid phase micro-extraction fibre (SPME) handling system utilising a Supelco (USA) divinyl benzene/carbowax/polydimethylsiloxane (DVB/ CAR/PDMS).…”
Section: Methodsmentioning
confidence: 99%
“…Non-targeted GC-MS headspace analysis. As previously described [17][18][19][20][21] , separation and quantification of phytochemical components were performed using a Shimadzu GC-2010 plus (USA) linked to a Shimadzu MSTQ8040 (USA) mass selective detector system as previously described 22 . Briefly, the system was equipped with a Shimadzu auto-sampler AOC-5000 plus (USA) fitted with a solid phase micro-extraction fibre (SPME) handling system utilising a Supelco (USA) divinyl benzene/carbowax/polydimethylsiloxane (DVB/ CAR/PDMS).…”
Section: Methodsmentioning
confidence: 99%
“…Herbaceous plants are a source of complementary and alternative remedies to conventional medications in treating several bacterial infectious diseases, including streptococcal pharyngitis (strep throat). Previous studies have demonstrated that numerous herbal extracts could act as antibacterial agents against S. pyogenes [10,34,35,36,37,38]. In the present study, we focused on 13 HWIs, known to Canadian traditional and indigenous healers who used them against sore throat.…”
Section: Discussionmentioning
confidence: 99%
“…Spices and herbs (flavor foods) comprise a large number of phytochemicals [39], which have been revealed to possess antimicrobial properties. For example, anti- S. pyogenes ability of phenolic compounds [40,41], flavonoids [35], alkaloids [42], terpenoids [43], and tannins [35] have been reported. Qualitative UPLC analysis in the present study for HWI revealed the presence of polyphenols, flavonoids, alkaloids, terpenoids, steroids, and tannins.…”
Section: Discussionmentioning
confidence: 99%
“…leaf extracts are potent inhibitors of Streptococcus pyogenes growth. 22 Several investigations have reported the chemical composition of B. acerifolius leaves and several interesting phytochemical components have been identified. The flavonoid content has been particularly well reported and apigenin-7-O-glucuronide ( Figure 1d), rutin (Figure 1e), luteolin-7-O-D-glucuronide ( Figure 1f), quercetin (Figure 1g), kaempferol (Figure 1h), luteolin ( Figure 1i) and apigenin ( Figure 1j) have been identified.…”
Section: Introductionmentioning
confidence: 99%